Repressive Actions of the State Security Against True Orthodox Church Structures in the Ukrainian SSR (1944–1953) - Vedeneev Dmitrii (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi, 2016)
In the article on the basis of unknown scientiﬁc community documents of the Soviet state security bodies provides an analysis of the objectives and key areas of operational work and repressive actions of the security services communities against True Orthodox Church (TOC) in the Ukrainian SSR in 1944–1953. The characteristic of agent and operational developments NKGB–MGB–KGB of the USSR against the so-called «catacomb Church», as a form of religious and social protest against aggressive atheistic policy of the Communist authorities, infringement of the rights of believers. The basic forms and methods of intelligence and operational activities of the security organs, aimed at creating informer positions in the environment of the communities of the TOC, making the split in the ranks of the adepts of secret religious sects, the collection of «compromising material» as the basis for the application of harsh repressive measures against the movement of the TOC. The authors pay special attention to the organization and personnel of units of the NKGB–MGB–KGB, engaged, according to the terminology, «the struggle with the Church-sectarian counterrevolution» and «Church-monarchist underground», a leading representative of which was considered in the TOC, particularly active in Chernihiv, Sumy, and Kharkiv oblasts of the Ukrainian SSR and the Donbass, and also in the neighboring regions of the Russian black soil region and the North Caucasus. Given the author’s periodization of the development of the catacomb movement, highlights the historical conditions of its creation and release in the USSR. Through the prism of intelligence documents examines the liturgical aspect of the TOC, its governing structure, forms of secrecy and concealment from the prosecution authorities, the position of the catacomb members in relation to social life and social structure in the USSR.